Towards a 'militarization rush' in the Arctic Region? Evidences, recent trends and critical issues in the case of the Russian Arctic - SORIANI S.; LANSETTI S. (2018)
This paper considers the most important elements concerning security and militarization in the Russian Arctic. Moscow is today re-opening and modernizing important military bases. This fact can support the idea that, from the Russian side, a new phase in the “militarization rush” is in progress. However, the militarization process is above all related to the need for Russia to patrol and protect about 23,000 km of borders, which are becoming more and more vulnerable in terms of national security, due to the process of ice melting. Moreover, after the collapse of the Soviet Union, the Russia navy and air force experienced a long period of decline; from this perspective, Russia's Government must invest in the military sector to maintain its position as superpower, in a strategic and global perspective. There are some important reasons that suggest that Russia is not interested, and does not have the capability to militarize further the Arctic: economic development requires stability; international relations in the Arctic has a long record of cooperation; ideology, that played a basic role during the Cold War is today less important; militarization is very costly and not sustainable; other security issues are emerging. It is the redefinition of security that makes the classical concept of militarization rather obsolete and not suitable to deal with the new Arctic security challenges.